Volume 2: Mechanics and Behavior of Active Materials; Structural Health Monitoring; Bioinspired Smart Materials and Systems; En 2018
DOI: 10.1115/smasis2018-8048
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of 3D-Printed Polycarbonate/Carbon Nanotube Nanocomposites

Abstract: Fused deposition modeling (FDM) is highly commercialized Rapid Prototyping (RP) technology for its ability to build complex parts with low cost in a short period of time. The process parameters in the FDM play a vital role in the mechanical properties of the polymeric parts. Most of the research studies show that the variable parameters such as orientation, layer thickness, raster angle, raster width, and air gap are some of the key parameters that affect the mechanical properties of FDM-processed polymeric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With an increase in the application of 3D printing, numerous researchers have focused on the mechanical properties of printed parts. Most of the reported studies have considered the standard mechanical testing methods and revealed the significant effect of print parameters on the tensile [29][30][31], flexural [32][33][34], and compressive [35][36][37] strengths. For more practical and structural applications of 3D-printed parts, the fracture mechanics of printed materials has recently grabbed significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in the application of 3D printing, numerous researchers have focused on the mechanical properties of printed parts. Most of the reported studies have considered the standard mechanical testing methods and revealed the significant effect of print parameters on the tensile [29][30][31], flexural [32][33][34], and compressive [35][36][37] strengths. For more practical and structural applications of 3D-printed parts, the fracture mechanics of printed materials has recently grabbed significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…The most useful nano-reinforcements are found to be CNTs, [110][111][112][113][114][115][116][117][118] CNF, 119 GO, 120 xGnP, 112,121,122 and nanoclays, 123 which are used with ABS, PLA, PEEK, PC, and PA12 polymers. Figure 12 summarizes the reported mechanical properties for different nanocomposites.…”
Section: Nanocompositesmentioning
confidence: 99%